STM imaging of electronic waves on the surface of Bi2Te3: topologically protected surface states and hexagonal warping effects. - Alpichshev, Z; Analytis, J; Chu, J; Fisher, I; Chen, Y; Shen, Z; Fang, A; Kapitulnik, A (2010)
Scanning tunneling spectroscopy studies on high-quality Bi2Te3 crystals exhibit perfect correspondence to angle-resolved photoemission spectroscopy data, hence enabling identification of different regimes measured in the local density of states (LDOS). Oscillations of LDOS near a step are analyzed. Within the main part of the surface band oscillations are strongly damped, supporting the hypothesis of topological protection. At higher energies, as the surface band becomes concave, oscillations appear, dispersing with a wave vector that may result from a hexagonal warping term.